Bersih desa : Tradisi Tahunan sebagai Wujud Rasa Syukur Masyarakat di Nagari Sitiung, Kecamatan Sitiung, Kabupaten Dharmasraya Sumatera Barat - Mohamad Hafrison; Ghefira Sabrina; Iksan Dwi Ganda Putra; Rohid Putra Abdullah; Dwi Andini; Rizky Maulana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Village cleaning is an annual tradition carried out by the people of Nagari Sitiung, West Sumatra, as a form of expression of gratitude for the harvest and abundance of sustenance. This tradition has local wisdom values ​​that have been passed down from generation to generation and are still preserved to this day. Village cleaning is generally carried out before the new planting season or after a large harvest, as an effort to maintain a harmonious relationship between humans, nature, and invisible forces that are believed to play a role in the balance of life. A series of activities in this tradition include working together to clean the village environment, joint prayer rituals, and various traditional events and traditional arts that are symbols of hope for blessings in the future. In this procession, the community shares roles and responsibilities, which shows the strong social ties between them. In addition, this tradition is an event for reflection and friendship, where migrants who return to their hometowns take part in the excitement of the event. The symbolic meaning of the village cleaning tradition lies not only in the ritual aspect, but also in the values ​​of togetherness, solidarity, and respect for ancestors. By maintaining this tradition, the people of Nagari Sitiung are trying to maintain their cultural identity amidst the changing times. The village clean tradition is also a reflection of the close relationship between humans and the environment, as well as a form of cultural adaptation that is rich in philosophical meaning. Through this tradition, the ancestral heritage remains alive as an important part of people's daily lives.